2013
DOI: 10.1111/jeb.12159
|View full text |Cite
|
Sign up to set email alerts
|

Environmental determinants of population divergence in life‐history traits for an invasive species: climate, seasonality and natural enemies

Abstract: Invasive species cope with novel environments through both phenotypic plasticity and evolutionary change. However, the environmental factors that cause evolutionary divergence in invasive species are poorly understood. We developed predictions for how different life-history traits, and plasticity in those traits, may respond to environmental gradients in seasonal temperatures, season length and natural enemies. We then tested these predictions in four geographic populations of the invasive cabbage white butter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 61 publications
3
47
0
Order By: Relevance
“…For example, in our P. rapae study populations, the mean number of generations per year varies from six (southern) to three (northern) in Japan and from five (southern) to two (northern) in North America. This latitudinal pattern in development time has been documented in a number of temperate insects (Nygren et al ., ; Blanckenhorn & Demont, b; Seiter & Kingsolver, ) and may be particularly likely in systems in which most or all populations can potentially complete multiple generations each year. However, rapid growth and development may also occur in high‐latitude and high‐altitude populations to complete a single generation over a short growing season (Roff, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in our P. rapae study populations, the mean number of generations per year varies from six (southern) to three (northern) in Japan and from five (southern) to two (northern) in North America. This latitudinal pattern in development time has been documented in a number of temperate insects (Nygren et al ., ; Blanckenhorn & Demont, b; Seiter & Kingsolver, ) and may be particularly likely in systems in which most or all populations can potentially complete multiple generations each year. However, rapid growth and development may also occur in high‐latitude and high‐altitude populations to complete a single generation over a short growing season (Roff, ).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, we focus here on three life history traits – body size, development time and immune function – and their phenotypic plasticity in response to rearing temperature. Previous studies in North America have documented population divergence in these life history traits and their reaction norms in P. rapae (Kingsolver et al ., ; Seiter & Kingsolver, ). In North America, high‐latitude populations have weaker immune responses, presumably due to reduced selection by Cotesia glomerata; we tested whether similar patterns of immune function exist in Japan.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the story of its expansion is unusual, and studying it in greater detail could considerably expand the knowledge of invasiveness, ecological patterns along latitudinal clines, and adaptations to novel environments. As observed by Seiter & kinGsolver (2013) "biotic invasions are natural experimental systems for studying the rapid evolution of traits and plasticity". Their argument is that novel environments place strong selection pressure on invasive species, resulting in new adaptations (seiter & KinGSolver 2013).…”
Section: Discussionmentioning
confidence: 99%
“…They showed that there was rapid evolutionary divergence along latitudinal gradients and geographical differentiation in development time. They also discovered that immune response and phenotypic plasticity were more closely related to latitudinal variation in season length and natural enemies than to variation in ambient temperatures (Seiter & kinGsolver 2013). It is important to note that native species can also adapt to environmental variation by evolving greater plasticity and that plasticity as well as trait values may vary along latitudinal gradients.…”
Section: Rapid Response To Natural Selectionmentioning
confidence: 99%
“…Climate change may affect population dynamics of different pest species, may increase outbreak frequency and may facilitate the shift of range to more northerly latitudes and higher elevations [6][7][8]. For example, northern expansion of the eastern spruce budworm, Choristoneura fumiferana in eastern North America may permit greater defoliation and mortality in extensive northern black spruce forests [9].…”
Section: Introductionmentioning
confidence: 99%